Writing immigration : scholars and journalists in dialogue - Suárez-Orozco, Marcelo M., 1956-; Louie, Vivian S.; Suro, Roberto (University of California Press, 2011)
"Bringing nuance, complexity, and clarity to a subject often seen in black and white, Writing Immigration presents a unique interplay of leading scholars and journalists working on the contentious topic of immigration. In a series of powerful essays, the contributors reflect on how they struggle to write about one of the defining issues of our time -- one that is at once local and global, familiar and uncanny, concrete and abstract. Highlighting and framing central questions surrounding immigration, their essays explore topics including illegal immigration, state and federal mechanisms for immigration regulation, enduring myths and fallacies regarding immigration, immigration and the economy, immigration and education, the adaptations of the second generation, and more."--Publisher's site